Effects of Insulin-degrading enzyme on the proliferation of swine Sertoli cells: Effects of IDE on Sertoli cells - Zhang, Mingrui; Gao, Hongmei; Sun, Yile; Liu, Zhiguo; Guo, Fei; Wang, Bingyuan; Mu, Yulian (Cellular and Molecular Biology, 2023)
Sertoli cells, the only somatic cells in testis seminiferous tubules, provide a supporting microenvironment for male germ cells and play essential roles in spermatogenesis. The insulin-degrading enzyme (IDE), a ubiquitous zinc peptidase of the inverzincin family, plays crucial role in sperm production, as IDE-knockout mice presented decreased testis weight and impaired sperm viability and morphology. However, whether and how IDE affects swine Sertoli cell proliferation remains unclear. Thus, in the present study, we aimed to evaluate the effects of IDE on the proliferation of swine Sertoli cells, as well as its underlying molecular mechanism. After knocking down IDE expression with small interfering RNA transfection, we analyzed the proliferation of swine Sertoli cells as well as the expression of related regulatory factors (WT1, ERK, and AKT). The results showed that IDE knockdown promoted swine Sertoli cell proliferation and increased WT1 expression, possibly through activating ERK and AKT. Overall, our findings suggest that IDE may be involved in male reproduction by regulating Sertoli cell proliferation, which provides new information to better understand the regulatory mechanisms of swine Sertoli cells and improve the reproductive traits of male pigs.